Developing guidelines and a theory of change framework to inform rewilding application - Hawkins, Sally; Convery, Ian; Carver, Steve (Frontiers in Conservation Science, 2024)
There remain a number of debates and conflicts about the concept of rewilding which can be barriers to its application. Some of these conflicts stem from the variety of contextual interpretations of rewilding, leading to conflict between rewilding theories and approaches.Conclusions have also been drawn about rewilding based on limited case studies, so that emergent rewilding theories aren't applicable to all rewilding projects, limiting their support in the field. Past theories have distinguished different types of rewilding, encouraging debate over the proposed methods, although in practice these approaches often share similar goals and use similar interventions. One barrier to achieving consensus in the practice of rewilding is that there are no clear guidelines for rewilding, and there are limited broad-scale studies focusing on how rewilding is practiced. This paper addresses this by offering the first broad study of rewilding guidelines and interventions, using data sourced from rewilding organisations, case studies, and research. Drawing from these data, the paper offers three tools to guide rewilding practitioners: (1) an overview of guidelines for rewilding practice, (2) a list of interventions used in rewilding, considering them against rewilding goals, (3) a theory of change framework to guide rewilding application. The tools presented here will inform work towards IUCN rewilding guidelines and suggests several areas that require further consideration. We hope that this initial study of application can improve agreement and collaboration among the rewilding community.